Of All Antioxidants, Would One Finally Be Used Clinically For Atherosclerotic Disease? - Suko Adiarto (Jurnal Kardiologi Indonesia, 2013)
Oxidation of LDL by oxygen free radicals results in unregulated uptake of modified LDL by macrophages in arterial wall. This is considered a key initiating factor for development and progression of atherosclerotic process. It is then logical to hypothesize that anti-oxidants, which can directly scavenge free radicals, can be useful in preventing atherosclerotic process. Initial support for this hypothesis accumulated rapidly from numerous in-vitro studies.